Biocontrol Mechanisms of Trichoderma longibrachiatum SMF2 Against Lanzhou Lily Wilt Disease Caused by Fusarium oxysporum and Fusarium solani - Xing Cao; Jiahui Liang; Ze Wu; Mingshun Zhang; Haiyan Li; Tao Liu; Wenxiu Yue; Yanan Wang; Liangbao Jiang; Guiqing Wang; Peibao Zhao; Yanrong Zhou; et al. (Horticulturae)
Lanzhou lily is a plant native to China with high edible, medicinal, and ornamental value that is relatively susceptible to Fusarium wilt. In this study, the application of Trichoderma longibrachiatum SMF2 (TlSMF2) effectively controlled Lanzhou lily wilt disease caused by Fusarium oxysporum and F. solani. TlSMF2 and the antimicrobial peptaibols trichokonins (TKs) produced by TlSMF2 inhibited the mycelial growth and spore germination of these two pathogens. Transcriptome analysis revealed that the TKs-induced defense responses of Lanzhou lily were mainly related to the production of plant hormones and defense enzymes. In detail, TKs treatment increased the levels of salicylic acid (SA) and jasmonic acid (JA) and the expression of their related genes and upregulated the activities of chitinase and phenylalanine ammonia-lyase (PAL). Moreover, TKs caused the induction of LzWRKY26 and LzWRKY75, which is highly homologous to LrWRKY3 that positively regulates Lilium regale resistance to F. oxysporum. LzWRKY26 expression was also induced by SA and MeJA treatments and F. oxysporum infection, which was consistent with the findings that many cis-acting elements associated with phytohormones and stress responses are present in the promoter region of LzWRKY26. Therefore, the biocontrol mechanisms of TlSMF2 against Lanzhou lily wilt disease involve substrate competition and toxicity against pathogens, as well as the induction of systemic resistance in plants. Our results highlight a promising biological control agent for soil-borne fungal diseases and offer deeper insights into the biocontrol mechanisms of TlSMF2.